Tiếp cận phương pháp máy học trong khai thác ý kiến khách hàng trực tuyến - Thái Kim , Phụng; Nguyễn An , Tế; Trần Thị Thu , Hà (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2020)
The study was conducted to apply supervised machine learning methods in mining online customer reviews. First, the study automatically collects 15,480 traveler reviews on hotels in Vietnam on Agoda.com website. Then, this study conducts the training process with machine learning models in order to find out the best model which is compatible with the training dataset and apply this model to forecast opinions for entire collected data. The results show that Logistic Regression (LR) and Support Vector Machines (SVM) methods have the best performance in Vietnamese language. This study is valuable as a reference for applications of opinion mining in the field of business.
Keywords: Opinion mining; Opinion classification; Opinion classification using machine learning